2004
DOI: 10.1002/hep.20474
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Leuprorelin and Flutamide in Male Patients With Hepatocellular Carcinoma Treated With Tamoxifen

Abstract: The growth of hepatocellular carcinoma (HCC) is thought to be dependent on androgens, as androgen receptors are present in most of these tumors. The aim of this multicenter trial was to assess the effect of antiandrogens in patients who have advanced HCC. Male patients with advanced HCC were randomized into 2 groups treated with (1) T reatment of patients who have symptomatic or advanced hepatocellular carcinoma (HCC) is still a challenge, because the mean survival is only a few months. 1 As curative treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Nevertheless, clinical trials using various anti-androgens in the attempt to treat HCC have inconsistent conclusions (Groupe d'etude et de traitement du carcinome, H., 2004, Matsuura et al, 1994, Chao et al, 1996). Several hypotheses have been proposed to elucidate this riddle, such as the fact that most of the anti-androgen therapies were developed to reduce/antagonize androgens from binding to AR, but not to target AR itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, clinical trials using various anti-androgens in the attempt to treat HCC have inconsistent conclusions (Groupe d'etude et de traitement du carcinome, H., 2004, Matsuura et al, 1994, Chao et al, 1996). Several hypotheses have been proposed to elucidate this riddle, such as the fact that most of the anti-androgen therapies were developed to reduce/antagonize androgens from binding to AR, but not to target AR itself.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed a male predominance in HCC, which suggested that androgen/AR signals may promote hepatocarcinogenesis (Yeh and Chen, 2010). However, the results from several clinical trials using various anti-androgens to treat HCC remain controversial (Groupe d'etude et de traitement du carcinome, H., 2004, Matsuura et al, 1994, Chao et al, 1996). Interestingly, Ma et al revealed that AR might suppress advanced-stage HCC metastasis using liver-specific deletion of AR (L-ARKO) mice model and in vitro HCC cell lines, and over-expressing AR with Sorafenib treatment could better suppress the HCC progression at late stages (Ma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Results from several studies on the use of anti-androgens to manage HCC remain controversial (Di Maio, et al 2008; Hépatocellulaire. 2004).…”
Section: Part II Androgen/ar Signaling In Liver Cancermentioning
confidence: 99%
“…Estrogens, including estradiol and diethylstilbestrol, have occasionally been employed to treat cancers, including HCC; however, both preventing and promoting cancer effect were recorded (Di Maio et al, 2006; Kalra et al, 2008; Lawrence et al, 2007). Androgens, including testosterone and dihydrotestosterone, have been shown to promote HCC; however, clinical research employing anti-androgens for HCC treatment had many disappointing consequences, with few beneficial effects or even worse survival for patients (Di Maio et al, 2008; Groupe d’Etude et de Traitement du Carcinome, 2004). Finally, a recent study reported dual yet opposing roles of hepatic AR: promoting HCC initialization and suppressing HCC metastasis (Ma et al, 2012).…”
Section: Molecular Mechanisms Of Sexual Dimorphism In Hccmentioning
confidence: 99%